2013
DOI: 10.1371/journal.pone.0073149
|View full text |Cite|
|
Sign up to set email alerts
|

PKD1 Mediates Negative Feedback of PI3K/Akt Activation in Response to G Protein-Coupled Receptors

Abstract: We examined whether protein kinase D1 (PKD1) mediates negative feeback of PI3K/Akt signaling in intestinal epithelial cells stimulated with G protein-coupled receptor (GPCR) agonists. Exposure of intestinal epithelial IEC-18 cells to increasing concentrations of the PKD family inhibitor kb NB 142­70, at concentrations that inhibited PKD1 activation, strikingly potentiated Akt phosphorylation at Thr308 and Ser473 in response to the mitogenic GPCR agonist angiotensin II (ANG II). Enhancement of Akt activation by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 63 publications
5
24
0
Order By: Relevance
“…In addition, inhibition of PKD by kb NB 142-70 or CRT006610 prevented ␤-catenin phosphorylation at Ser 552 , but enhanced Akt activation, as shown by the increase in the phosphorylation of the Akt substrate PRAS40 at Ser 246 (data not shown). These results are consistent with the notion that PKD mediates negative feedback on PI3K/ Akt activation in GPCR-stimulated intestinal epithelial cells (36). Accordingly, treatment with the Akt inhibitor GSK690693 suppressed ANG II-induced phosphorylation of PRAS40 at Ser 246 (data not shown), but did not prevent ␤-catenin Ser 552 phosphorylation in response to ANG II (Fig.…”
Section: Gpcr/pkd1 Activation Induces ␤-Catenin Phosphorylation At Sesupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, inhibition of PKD by kb NB 142-70 or CRT006610 prevented ␤-catenin phosphorylation at Ser 552 , but enhanced Akt activation, as shown by the increase in the phosphorylation of the Akt substrate PRAS40 at Ser 246 (data not shown). These results are consistent with the notion that PKD mediates negative feedback on PI3K/ Akt activation in GPCR-stimulated intestinal epithelial cells (36). Accordingly, treatment with the Akt inhibitor GSK690693 suppressed ANG II-induced phosphorylation of PRAS40 at Ser 246 (data not shown), but did not prevent ␤-catenin Ser 552 phosphorylation in response to ANG II (Fig.…”
Section: Gpcr/pkd1 Activation Induces ␤-Catenin Phosphorylation At Sesupporting
confidence: 90%
“…These cells express G q-coupled receptors for angiotensin II (ANG II) and vasopressin (3-6, 44, 73, 78) and have been extensively used as a model system to examine signal transduction pathways in response to GPCR activation (3-6, 54, 56, 73, 79). Stock cultures of IEC-18 cells were maintained as described previously (36,54). Briefly, cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 5% fetal bovine serum and penicillinstreptomycin and kept at 37°C in a humidified atmosphere containing 10% CO 2 and 90% air.…”
Section: Cell Culturementioning
confidence: 99%
“…5, D sibility, we used two structurally unrelated selective inhibitors of PKD activity, CRT0066101 (58) and kb NB 142-70. In previous studies, we demonstrated that these inhibitors block PKD activation and DNA synthesis in IEC-18 cells (36,38,59,60). As shown in Fig.…”
Section: Gpcr Agonists Induce Rapid Increase In the Phosphorylationmentioning
confidence: 65%
“…These cells exhibit a number of features similar to normal cells in culture, including a normal rat diploid karyotype, a strong density inhibition of growth, a lack of growth in soft agar, and resemble stem/progenitor cells (74). Cultures of IEC-18, IEC-6, and CaCo-2 cells were maintained as described previously (36,60). Briefly, cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal bovine serum (FBS) and penicillin/ streptomycin, and kept at 37°C in a humidified atmosphere containing 10% CO 2 and 90% air.…”
Section: Methodsmentioning
confidence: 99%
“…7A,B). The importance of PKD phosphorylation to the assembly of the shuttling complex was verified by inhibition of PKD activity with 10 µM kb NB 142-70 (Ni et al, 2013), which indeed prevented the assembly of ERK1c with PI4KIIIβ but not with 14-3-3γ, as assessed by a co-immunoprecipitation assay (Fig. 7C,D) and by PLA (Fig.…”
Section: Pi4kiiiβ Phosphorylation By Pkd1 Regulates Its Binding To Erk1cmentioning
confidence: 80%